Prevalence and Characteristics of the O122 Pathogenicity Island in Typical and Atypical Enteropathogenic Escherichia coli Strains - Vieira, Mônica A. M. (American Society for Microbiology (ASM), 2010)
The presence of the pathogenicity island (PAI) O122 genes, efa1 (lifA), sen, pagC, nleB, and nleE, in typical and atypical enteropathogenic Escherichia coli (EPEC) strains was investigated. The simultaneous occurrence of all genes was statistically associated with diarrhea due to atypical EPEC. Detection of the complete PAI O122 could aid in the identification of potential pathogenic strains of atypical EPEC.